Drivers of freshwater fish colonisations and extirpations under climate change. Issue 5 (6th October 2014) - Conti, Lorenza; Comte, Lise; Hugueny, Bernard; Grenouillet, Gaël
<x xml:space="preserve">Abstract</x> Climate change is expected to bring about profound rearrangement of ecological communities by affecting individual species distributions. The resulting communities arise from the idiosyncratic responses of species to future changes, which ultimately relate to both shrinking and expanding species ranges. While spatial patterns of colonisation and extirpation events have received great attention, the identification of specific drivers remains poorly explored. This study aims to investigate the relative contribution of species gain and loss to the turnover of fish assemblages in French rivers under future climate change, and to identify their principal drivers. Future projections of potential habitat suitability in 2080 derived from species distribution models for 40 fish species showed that colonisations and extirpations could play counterbalancing roles in the reshuffling of communities. Simultaneously, these two processes exhibited patchy spatial patterns, segregated along the longitudinal and altitudinal gradients, resulting in dramatic species turnover of ∼ 60% of the current composition of species assemblages. Beyond the effect of topographic location, colonisations were found to be driven by temperature seasonality while extirpations were affected by modifications in both thermal and precipitation regimes. These results generate the possibility of developing ecosystem‐based management tools focused on the early identification of areas where particular species may be sensitive to climate changes. Disentangling the drivers of colonisation and extirpation processes provides ready‐to‐use information that may be easily integrated into conservation planning. This information could be used to identify potential hotspots of species gain and loss and to then compare these hotspots with newly favourable areas so as to consider their actual accessibility in order to facilitate future range shifts.